Scaled Fracture Toughness Based on the Weibull Stress for the Ferritic Steel Used in Nuclear Power Plants - Jin, Weiya; Li, Yan; Li, Yuebing; Zhou, Mingjue (Frontiers in Materials, 2022)
As an important material property in structural integrity assessment of nuclear power components, fracture toughness can be measured by single edge-notched bend (SENB) specimens or compact tension (CT) specimens. However, the tested values may be inhomogeneous with the crack size and specimen thickness. Some toughness scaling models (TSM) were proposed to transfer the tested value to fracture toughness under small-scale yielding. Combined with the tested data by SENB specimens with different crack sizes and CT specimens with different thickness, the scaled fracture toughness is investigated on the global and local approach to fracture. Using the scaled values of toughness, the Weibull scale parameter K0 is estimated and compared for the ferritic steel DIN 22NiMoCr37 widely used in nuclear power plant. The results show that the estimated scale parameter K0 using the scaled toughness obtained by the global approach on the J-Q theory is reasonable in agreement with that by the local approach on the Weibull stress with the relative error of about 10%.